Analisis Implementasi Akad Pembiayaan KPR Pada Nasabah Berpenghasilan Rendah (KPR BTN Subsidi) Di Bank BTN Kantor Cabang Syariah Medan - Anggrie NST, Silvia; Syahriza, Rahmi; Inayah, Nurul (Jayapangus Press, 2025)
The aim of this research is to determine the implementation of KPR financing contracts for low-income customers at Bank BTN KC Syariah Medan and financing provisions for customers whose income is less than the minimum limit. Qualitative research is the methodology employed. Both primary and secondary data sources were employed. Semi-structured interviews are the method utilized to acquire the data. The study's findings show that Bank BTN KC Syariah Medan's implementation of the KPR financing agreement for low-income customers complies with DSN-MUI Fatwa No.04/DSN-MUI/IV/2000 because, prior to entering into a murabahah agreement with a customer, Bank Tabungan Negara (BTN) KC Syariah Medan asks the customer to sign a wakalah letter. The bank then purchases the desired home from the developer, acquires the home, and then sells the home to the customer using the murabahah agreement. Customers whose income is less than the specified minimum limit can still finance Subsidized KPR with additional income (double income), and attach proof of the husband and wife's income (double income) at the time the financing process is carried out. This is done by Bank BTN as a form of solution and convenience for customers who earn less than the minimum limit so they can still get a house to live in.